Efektivitas Intervensi Colek dalam Peningkatan Perilaku Patient Safety - Nurhasanah Nurhasanah; Erwin Purwaningsih; Dewi Mardahlia; Restu Yunus (Jurnal Kesehatan Indonesia, 2021)
Patient safety is an important issue in global hospital services. One of the factors related to patient safety is the patient safety behavior of the medical staff, including nurses as health workers with the largest proportion in hospitals. This study aimed to determine the effectiveness of Colek intervention to improve patient safety behaviors of hospital nurses in Samarinda City. This experimental research used a pretest-posttest control group design. The samples were 60 people that were divided into two groups. Group A received an intervention in the form of a patient safety book, and group B received an intervention with a patient safety book and the Colek intervention. Colek intervention was an education program focusing on expanding knowledge, increasing awareness, developing leadership skills, and improving patient safety behavior. The data were analyzed using the Wilcoxon test and Mann-Whitney test. This study found that the mean of pretest in group A and group B had the same score (38,5 with an SD of 31,5). The mean post-test in group A was 46,0 with an SD of 57,5 while the mean of post-test in group B was 63,0 with an SD of 71,0. The results of this study showed a significant difference (p=0,001) between before and after the intervention using the patient safety book. A significant difference (p=0,000) was also found between before and after the intervention using the patient safety book and the Colek intervention. The Colek intervention was an effective way to improve the patient safety behavior of the hospital nurses in Samarinda City.